PENERAPAN VARIASI TEMPAT DUDUK PADA PEMBELAJARAN TEMATIK DI KELAS IV MI TARBIYYATUL ARIFIN LOWOKSURUH - Zuhriatul Fuadah; Mohammad Afifulloh; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Madrasah Ibtidaiyah Tarbiyyatul Arifin Malang is one of the school located in kecamatan pakis mangliawan village School is located on main road which easy to reach people about. Variation seating is one effort in managing, class many of the seats that could be used to require creative teaching style in choosing the appropriate for the conditions in class and matter will be given. Not in keeping the variation seating sometimes can also hinder understanding. learning material to students. Which researchers prefer to focus research on, planning the application of the use of seat and obstacles variations in learning thematic in class IV in MI Tarbiyyatul Arifin Lowoksuruh. Type this research is qualitative study, research kualitatif.pada theory limited to systematic sense a question pertaining to a set of a proposition derived from data back empirically tested.At the focus is organizing planning: the learning environment in class.Mengkondisikan ready for students learn in class.Classrooms and the seat. Related to the variation a seat in learning the fourth thematic research in class employing variations a seat u-shaped, all this in mark with students more eager than by the seating of traditional or conventional.And students more creative and active in. Obstacles the variation in a seat in learning thematic fourth grade students is the beginning of a seat to move variation as their students feel comfort while pembalajarn, and students many out of class when apply variasai the seat.Keywords: Variation a seat, thematic, fourth grade